ANALISIS PENGARUH GENDER DAN TINGKAT PENDIDIKAN MAHASISWA AKUNTANSI DENGAN LOVE OF MONEY SEBAGAI VARIABEL INTERVENIG (Studi Kasus Mahasiswa Akuntansi Universitas Islam Malang Dan Mahasiswa Politeknik Negri Malang) - Dinda Septian Nur’aini; Nur Diana; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2021)
This study was conducted to determine the effect of gender and education level on the ethical perception of a student with love of money as an intervening variable. This type of research is quantitative research. The data used in this study are primary data. Respondents were 100 students at the Malang Islamic University and the Malang State Polytechnic using a questionnaire. The results of this study indicate that the gender variable has an effect on love of money. and also the results of this study indicate that love of money affects the ethical perception of accounting studentsKeywords: gender, education level, ethical perception, love of money.